Identification of QTL for Pre-harvest Sprouting Resistance by Using Chromosome Segment Substitution Lines of Dongxiang Common Wild Rice - Jiaxiao HU; Jin LIU; Xiaoding MA; Hang TU; Huiying ZHOU; Bingxin MENG; Di CUI; Maomao LI; Longzhi HAN; Liqin YU (Guangdong nongye kexue)
【Objective】High-temperature and rainy weather lead to pre-harvest sprouting (PHS), severely impacting yield and quality traits of rice. Identification and screening of germplasm or genetic resources is a fundamental pathway for developing new varieties resistant to PHS and eliminating PHS damage.【Method】In the study, a set of chromosome segment substitution lines (CSSLs) derived from Dongxiang wild rice ('C35') as the donor parent and 'Nipponbare' ('NIP') as the recipient parent were used as the experimental materials, and then PHS resistance were evaluated and QTLs were mapped in 2021-2023, with an aim to screen PHS germplasm and identify major QTLs.【Result】Dongxiang wild rice 'C35' exhibited strong dormancy under different environments with a pre-harvest sprouting rate (PHSR) of 0.00%; 'Nipponbare' showed significant PHS with an average PHSR of 31.95%. The PHSR varied widely among CSSL populations, the phenotypic repeatability of PHSR was relatively high in different years, and ten lines from the CSSL populations with strong dormancy and resistance to PHS were screened. A total of 14 QTLs controlling the PHSR were detected, and four QTLs were repeatedly detected under different environments. These QTLs formed four QTL clusters (qPHSRC1, qPHSRC2, qPHSRC8 and qPHSRC9), among which qPHSRC2 and qPHSRC9 had higher LOD values, phenotypic contribution rate (%) and additive effect, and qPHSRC2 was a newly discovered major QTL cluster.【Conclusion】A batch of PHS resistant germplasms were screened and 14 QTLs were mapped, four QTL clusters were repeatedly identified, and a new major QTL cluster qPHSRC2 controlling the PHSR was discovered.